Rapid and fully automated bacterial pathogen detection on a centrifugal-microfluidic LabDisk using highly sensitive nested PCR with integrated sample preparation1. Issue 18 (21st September 2015) - Czilwik, G.; Messinger, T.; Strohmeier, O.; Wadle, S.; von Stetten, F.; Paust, N.; Roth, G.; Zengerle, R.; Saarinen, P.; Niittymäki, J.; McAllister, K.; Sheils, O.; et al.
<x xml:space="preserve">Abstract</x> Integrated PCR LabDisk and portable LabDisk-Player.